Penerapan Model Phonics Berbantuan Media Video Animasi Canva dalam Meningkatkan Kemampuan Membaca Permulaan Siswa Sekolah Dasar - Dara Baldevi Lubis; Sarah Fazilla; Misrina (Indonesian Journal of Elementary Education and Teaching Innovation, 2026)
This study aims to analyze the effect of the application of the Canva-based animated video-assisted Phonics model on the initial reading ability of elementary school grade I students. This study uses a quantitative approach with a quasi-experimental design of the nonequivalent control group design. The research sample amounted to 40 students consisting of 20 students in the experimental group and 20 students in the control group. The data collection technique used the initial reading ability test through pre-test and post-test, which was analyzed using normality, homogeneity, and t-test tests. The results showed that the initial ability of the two groups was relatively similar, with an average pre-test of 56.25 in the experimental group and 55.75 in the control group. After treatment, the average post-test of the experimental group increased to 82.50 (very good category), while the control group became 68.00 (good category). The t-test results showed a significance value of 0.000 < 0.05, which means there was a significant difference between the two groups. The N-Gain value of the experimental group was 0.60 (medium–high category), higher than that of the control group of 0.28 (low category). Thus, the application of the Canva-based animated video-assisted Phonics model is effective in improving the early reading skills of elementary school students through increased motivation and learning engagement.